Bivalves and evolutionary resilience: Old skills and new strategies to recover from the P/T and T/J extinction events - Ros, Sonia (2011)
Diversity dynamics among bivalves during the Triassic and Early Jurassic provides the opportunity to analyse the recovery patterns after two mass extinctions: Permian/Triassic and Triassic/Jurassic (T/J). The results presented here are based on a newly compiled worldwide genus-level database and are contrasted to the main morphological characters of the different taxonomical (orders and their constituent families and genera) and ecological groups. Many of such morphological characters are innovations appearing during the time span considered. Diversity and evolutionary rates were assessed and compared between these groups. During the Early Triassic there was a slow recovery, dominated by epifaunal taxa, the order Pectinida being the most diverse. The major post-Permian radiation took place during the Anisian, with several morphological and ecological innovations appearing and/or diversifying. The Late Triassic was a time of great diversification and ecological specialisation. Although the T/J was a true mass extinction for bivalves, it was not indiscriminate as its impact was stronger on specialised orders and not all ecological categories were equally affected. Recovery during earliest Jurassic was fast, confirming the high-evolutionary resilience of bivalve molluscs, except for groups with thick shells and tropical distribution, probably because of a biocalcification crisis.